PENGARUH RIGHT ISSUE TERHADAP ABNORMAL RETURN DAN VOLUME PERDAGANGAN SAHAM PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2013 - FIRSTOLINO, MUHAMMAD (Jurnal Akuntansi AKUNESA, 2016)
The purpose of this research is analyze effect the announcement of the right issue on the capital market Indonesia (BEI) in 2013. The data used in this study is date of the company that announced a rights issue, daily stock price data, daily stock trading volume data, the data number of shares outstanding, JCI share data The statistical method used to test the hypothesis is Paired Sample T-Test. The model used to determine the estimated returns in this research is the Market Adjusted Model. The result of this research showed that there were no significant differences from the abnormal return with a significant 0,634 > 0,05 and trading volume activity with a significant 0,064 > 0,05 at the time before and after the announcement of the right issue. This means that the right issue announcement does not contain meaningful information for investor to change their investment preferences.